Scoliosis in RETT Syndrome: A National Referral Centre Experience. Issue 2 (17th March 2023) - Menachem, Shay; Hershkovich, Oded; Ackshota, Nissim; Friedlander, Alon; Givon, Uri; Ben-Zeev, Bruria; Caspi, Israel
Abstract : Study Design: This was a retrospective case series. Objective: The objective of this study was to discuss the treatment challenges in scoliosis patients with Rett syndrome (RTT) in a national referral centre for RTT. We describe structural characteristics of curves, age of onset, genetic mutation, ambulation status, and treatment through RTT progression. Based on this unique experience, we aimed to suggest guidelines for scoliosis treatment in RTT patients. Summary of Background Data: RTT is a neurodevelopmental disorder associated with a mutation in the methyl-CpG binding protein 2 (MECP2) gene, primarily in females with significant features of growth failure, gastrointestinal and pulmonary dysfunction, ataxia, seizures, and intellectual disability. Scoliosis is the most common orthopedic manifestation of RTT and is present in 64%–75% of patients. No clear guidelines for scoliosis treatment in RTT are available, and typically patients are treated according to guidelines of another neuromuscular scoliosis. Methods: Clinical and radiographic data were gathered, including MECP2 mutation type, scoliosis characteristics, preoperative treatment, surgical treatment, functional status, and postoperative follow-up. Results: Our cohort included 102 patients with RTT. They were 36 who presented with scoliosis; 18 were treated surgically. C-curve was found in 17 patients and S-type in 19. Scoliosis treatment onset was 8.76 years in the C-type group and 13.88 years in the S-type group. The average curve at the time of surgery was 52.42 degrees. The average time until surgery was 2.44 years. Seventeen patients underwent posterior spinal fusion, and 1 patient underwent posterior spinal fusion+anterior spinal fusion with an average correction of 40 degrees. The most common mutation was R255X nucleotide (30% of cases). The most severe curves had mutations R168X and R270X nucleotides. Conclusions: We advise early monitoring for patients with RTT and scoliosis due to early and rapid progression. Common mutations found were R255X, R168X, R270X, and T158M. We recommend surgical treatment in every curve above 45 degrees, independently of age.